Border identifications narratives of religion, gender, and class on the U.S.-Mexico border - Vila, Pablo 1952- (Univ. of Texas Press, 2005)
"An ethnography that explores the role of religion, gender, and class in the formation of social identity on both sides of the US-Mexico border. A continuation of the study Vila began in Crossing Borders, Reinforcing Borders"--Provided by publisher.
"An ethnography that explores the role of religion, gender, and class in the formation of social identity on both sides of the US-Mexico border. A continuation of the study Vila began in Crossing Borders, Reinforcing Borders"--Provided by publisher.
Includes bibliographical references and index
Keywords: Identité collective - Mexican-American Border Region; Identité collective - Mexique - Ciudad Juárez; Identité collective - Texas - El Paso; Group identity -- Mexico -- Ciudad Juárez; Group identity -- Texas -- El Paso; Group identity -- Mexican-American Border Region; Grenzgebiet; Identität; Ciudad Juárez (Mexique) - Conditions sociales; El Paso (Tex.) - Conditions sociales; Mexican-American Border Region - Conditions sociales; Mexiko; Ciudad Juárez (Mexico) -- Social conditions; El Paso (Tex.) -- Social conditions; Mexican-American Border Region -- Social conditions; USA